Procyanidin B2 Protects TR-iBRB2 Cells Against Hyperglyc emia Stress by Attenuating Oxidative Stress and Inflammasome Activation via Regulation of Redoxosomes/NF-kB Signaling - Zou, Wenjun; Lu, Qianyi; Zhu, Xue; Pan, Ying; Xu, Quan; Wang, Ke (Current Molecular Medicine, 2023)
Background: Microvascular dysfunction is a hallmark of diabetic retinopathy (DR), which may lead to visual impairment and blindness. Procyanidin B2 (PB2) is a subclass of flavonoids and is widely known due to its anti-oxidant and antiinflammatory effects. However, little is known about the effect of PB2 on hyperglycemia stress-induced retinal microvascular dysfunction. Objective: The purpose of this study was to investigate the effect of PB2 against hyperglycemia stress in rat retinal capillary endothelial cells (TR-iBRB2) as well as the underpinning mechanism. Methods: Cell viability was determined using MTT assay. ROS, NOX activity analysis, Western blot analysis, and immunofluorescence analysis were applied in the study. Results: The results showed that PB2 pre-treatment significantly reduced high glucose- induced cytotoxicity in TR-iBRB2 cells by suppressing oxidative stress and inflammasome activation. Mechanistical study revealed that redoxosomes were formed and activated in TR-iBRB2 cells upon hyperglycemia stress, resulting in activation of NF- ΚB and thus induction of oxidative stress and inflammasomes activation. However, PB2 pre-treatment dose-dependently attenuated the above events, indicating the protective effect of PB2 against hyperglycemia stress was achieved by regulating redoxosomes/ NF-kB signaling. Conclusion: Our findings may contribute to the potential clinical use of PB2 in treating DR and suggest redoxosomes/NF-kB signaling may be a potential therapeutic target of this disease.
Keywords: Diabetic retinopathy